Investigation and Analysis on the Factors Influencing the Use of E-Commerce for Marketing SMEs’ Dairy Products: A Case Study at SUSDAGTEL SMEs in Bengkulu, Indonesia - Ridha Rizki Novanda; Helfi Eka Saputra; Basuki Sigit Priyono; Sriyoto Sriyoto (Caraka Tani: Journal of Sustainable Agriculture, 2022)
During the pandemic, inadequate knowledge in e-commerce is one of the obstacles in the e-commerce system. As a result, it is critical to examine the determinants of dairy product marketing using e-commerce during social distancing. This study aims to analyze the factors of SMEs’ dairy product marketing using e-commerce during social distancing. The research was conducted in Bengkulu, with 31 respondents who were members of the milk, meat and eggs association (SUSDAGTEL). The respondent groups were selected purposively to identify the factors using e-commerce. The data analysis was carried out quantitatively, which is determining the influencing factors with partial least square tools. The results of hypothesis testing have shown that external factors and technological factors do not affect the use of e-commerce in marketing SMEs’ dairy products, while both the performance of SMEs and the orientation readiness affect the use of e-commerce in SMEs. The SME performance has a significant effect on the use of e-commerce with a P-value of 0.000. The organizational readiness factor has a significant effect on the use of e-commerce with a P-value of 0.009. SME actors are elevated to the highest level of priority in the strategy's implementation. Small and medium-sized enterprises (SMEs) play a critical role in advancing the use of e-commerce in dairy product marketing.